The Effect of Bitter Melon Leaves (Momordica Charantia L) Ethanol Extract on the Trichophyton Rubrum Fungal Inhibiting Zone of Diffusion Method - Slamet (POLTEKKES KEMENKES PONTIANAK, 2020)
The bitter melon plant (Momordica charantia L) has medicinal properties. Bitter melon leaves contain secondary metabolites such as flavonoids, tannins, saponins, and alkaloids. The compound has anti-fungal properties. This study aims to determine the effect of ethanol extract of bitter melon leaves (Momordica charanthia L) on the inhibition zone of the fungus Trichophyton rubrum diffusion method. The research method used was a quasi-experiment with a purposive sampling technique. The population in this study were bitter melon extract made with criteria of old leaves (obtained from bitter melon plants), 5th leaf from shoot to base, green leaves, non-rot leaves, non-ripped leaves and not eaten by caterpillars that have taken in Rasau Jaya Village 1, Rasau Jaya District, Bina Karya Hamlet. The sample used in this study was pared leaf extract (Momordica charantia L) using ethanol solvent with a concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% and 90% using Dimethyl Sulfoxide as thinner. Analysis of the Linear Regression Test obtained the value (p = 0.00 <0.05), then Ha was accepted meaning that there was an influence of ethanol extract of the bitter melon leaf (Momordica charantia L) on the inhibition zone of the fungus Trichophyton rubrum by the diffusion method. The results of R Square (R2) which amounted to 0.930 showed that the magnitude of the contribution of the concentration of bitter melon leaf extract in influencing the inhibitory zone of the fungus Trichophyton rubrum was 93%.